Aesthetic Breast Shape Preferences Among Plastic Surgeons. Issue 6 (June 2015) - Broer, Peter Niclas; Juran, Sabrina; Walker, Marc E.; Ng, Reuben; Weichman, Katie; Tanna, Neil; Liu, Yuen-Jong; Shah, Ajul; Patel, Anup; Persing, John A.; Thomson, James Grant
Abstract : Background: There has been little discussion in the plastic surgery literature regarding breast shape preferences among plastic surgeons, despite strong evidence that such aesthetic preferences are influenced by multiple factors. Much effort has been focused on delineating the objective criteria by which an "attractive" breast might be defined. This study aimed at providing a better understanding of the presence and significance of differences in personal aesthetic perception, and how these relate to a plastic surgeon's demographic, ethnic, and cultural background, as well as practice type (academic vs private). Methods: An interactive online survey was designed. Modifiable ranges of upper pole fullness and areola size were achieved via digital alteration, enabling participants to interactively change the shape of a model's breasts. The questionnaire was translated into multiple languages and sent to plastic surgeons worldwide. Demographic data were also collected. Analysis of variance was used to elucidate plastic surgeon's breast shape preferences in respect to sex and age, geographic and ethnic background, as well as practice type. Results: The authors gathered 614 responses from 29 different countries. Significant differences regarding preferences for upper pole fullness, areola size in the natural breast, and areola size in the augmented breast were identified across surgeons from the different countries. Further, significant relationships regarding breast shape preferences were distilled between the age and sex of the surgeon, as well as the practice type. No differences were found in respect to the surgeons' self-reported ethnic background. Conclusions: Country of residence, age, and practice type significantly impact breast shape preferences of plastic surgeons. These findings have implications for both patients seeking and surgeons performing cosmetic and reconstructive breast surgery. In an increasingly global environment, cultural differences and international variability must be considered when defining and publishing new techniques and aesthetic outcomes. When both the plastic surgeon and the patient are able to adequately and effectively communicate their preferences regarding the shape and relations of the breast, they will be more successful at achieving satisfying results.